RASIONALISME ISLAM BERAWAL DARI BAHASA - Soleh, A. Khudori (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2007)
It is a fact Greek philosophy has given great contribution for Islam philosophy growth. However, it does not mean that Islamic philosophy is Greek rubbing, because Islam philosophy really unlike Greek philosophy. Others, in reality, philosophy of Greek does not inspire many Islamic philosophy, moreover, majority of Islam people did not accept it. Only, some figure take and develop their philosophy based did not accept it. Only some figure and develop their philosophy based on Greek line. Sincerely, Islamic philosophy was born from thought and the treasure of Islamic science itself. It emerged from rationalization of Arab Language, then it pusped appearance rationalize of any object study, such as: jurisprudence and theology. Surely, it is triggered by existence of challenge and attacking from rationality of outside party. All have pushed all Moslem thinkers to develop rational method, and this exactly, which give road for entry of Greek philosophy in Islam society.